2018
DOI: 10.5194/esd-9-33-2018
|View full text |Cite
|
Sign up to set email alerts
|

Process-level improvements in CMIP5 models and their impact on tropical variability, the Southern Ocean, and monsoons

Abstract: Abstract. The performance of updated versions of the four earth system models (ESMs) CNRM, EC-Earth, HadGEM, and MPI-ESM is assessed in comparison to their predecessor versions used in Phase 5 of the Coupled Model Intercomparison Project. The Earth System Model Evaluation Tool (ESMValTool) is applied to evaluate selected climate phenomena in the models against observations. This is the first systematic application of the ESMValTool to assess and document the progress made during an extensive model development … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 109 publications
(124 reference statements)
1
15
0
Order By: Relevance
“…For CMIP6 models, Zelinka et al (2020) showed that cloud feedbacks and thus ECS in high-sensitivity models are dominated by changes in clouds over the Southern Ocean, while in CMIP3 and CMIP5 the uncertainty in cloud feedbacks is dominated by clouds in the subtropical subsidence regions. One might speculate that a possible reason for this might be an improved simulation of clouds over the Southern Ocean in some models (Bodas-Salcedo et al, 2019;Gettelman et al, 2019a) as shown for some pre-CMIP6 model versions evaluated by Lauer et al (2018). The findings of Zelinka et al (2020) could also at least partly explain the larger inter-model spread in climate sensitivity due to more and different regions / clouds types dominating the cloud feedbacks resulting in a weaker emergent constraint compared with CMIP5 models.…”
Section: Discussionmentioning
confidence: 97%
“…For CMIP6 models, Zelinka et al (2020) showed that cloud feedbacks and thus ECS in high-sensitivity models are dominated by changes in clouds over the Southern Ocean, while in CMIP3 and CMIP5 the uncertainty in cloud feedbacks is dominated by clouds in the subtropical subsidence regions. One might speculate that a possible reason for this might be an improved simulation of clouds over the Southern Ocean in some models (Bodas-Salcedo et al, 2019;Gettelman et al, 2019a) as shown for some pre-CMIP6 model versions evaluated by Lauer et al (2018). The findings of Zelinka et al (2020) could also at least partly explain the larger inter-model spread in climate sensitivity due to more and different regions / clouds types dominating the cloud feedbacks resulting in a weaker emergent constraint compared with CMIP5 models.…”
Section: Discussionmentioning
confidence: 97%
“…The positive temperature bias over the Southern Ocean, however, seems to have gotten worse in time (Hyder et al, 2018) with the CMIP6 multimodel mean showing larger biases than in the two previous CMIP phases. Regional absolute biases in surface temperature of up to 6°C as seen in CMIP5 and some pre‐CMIP6 models (Lauer et al, 2018) are still present in CMIP6.…”
Section: Systematic Biasesmentioning
confidence: 92%
“…There are many different, model‐dependent causes for biases in modeled surface temperature. Common causes include biases in downward shortwave radiation at the surface because of errors in simulated cloud properties (Hyder et al, 2018; Lauer et al, 2018), errors in oceanic circulation (Kuhlbrodt et al, 2018), errors in the simulation of trade winds (Lauer et al, 2018), and errors in surface albedo and moisture propagated from the vegetation schemes (Séférian et al, 2016). Even though the multimodel mean of the surface temperature bias shows only small improvements in CMIP6, some individual models made significant progress (Danabasoglu et al, 2020).…”
Section: Systematic Biasesmentioning
confidence: 99%
“…Comparing model results to observations provides insight into the quality of model simulations and the way in which various processes are represented. Comparisons with observations can reveal shortcomings in individual models and systematic errors in a large multimodel ensemble 7,20 . An example of a systematic error is the excessive simulated band of precipitation in the tropical Pacific south of the Equator, a feature not present in observations.…”
Section: From Model Errors To Understanding Processesmentioning
confidence: 99%